The Meaning of Life of a Digital Commercial Sex Worker Using the MiChat Application in Gresik Regency: A Logotherapy-Based Intrinsic Case Study - Ziadatur Rif'ah; Ima Fitri Sholichah (IJIP : Indonesian Journal of Islamic Psychology, 2026)
The rapid development of digital technology has transformed the landscape of commercial sex work, including through the MiChat application in Gresik Regency, a region known for its strong religious identity. This study aims to explore the meaning of life experienced by digital commercial sex workers who operate through MiChat in Gresik. The study employed a qualitative intrinsic case study approach using in-depth interviews and observation as data collection techniques. The participant was a 29-year-old woman (Subject L) who had been active as a digital commercial sex worker via MiChat. Data were analyzed thematically based on Viktor Frankl’s logotherapy framework, particularly the dimensions of freedom of will, will to meaning, and meaning of life. The findings reveal that Subject L’s involvement in digital sex work emerged from multiple interconnected factors, including family instability, early sexual trauma, economic pressure, and the accessibility provided by digital technology. Despite these difficulties, the participant demonstrated self-reflection, selective self-regulation in client interactions, and aspirations for a more meaningful future life involving emotional stability and family life. Meaning in life was constructed through survival strategies, creative values reflected in nail art activities, interpersonal experiences, and spiritual reflection amid feelings of guilt and social stigma. This study contributes to a deeper understanding of the existential experiences of marginalized individuals in digitally mediated environments. However, the findings are limited to a single intrinsic case study and are not intended for broad generalization.